New developments in the Gd3+/Sm3+ ions doped lithium aluminum borate glasses of luminescent materials for lighting applications. (November 2022) - Rittisut, W.; Mool-am-kha, P.; Wantana, N.; Ruangtaweep, Y.; Rujirawat, S.; Kidkhunthod, P.; Manyum, P.; Yimnirun, R.; Prasatkhetragarn, A.; Kothan, S.; Kim, H.J.; Kaewkhao, J.
Abstract: The standard melt-quenching technique was used to create a novel series of Gd 3+ and Sm 3+ co-doped borate glasses with the LAGdxBSm1.0 and LAGd2.5BSmx series of glasses. All samples were analyzed by XRD, FTIR, and optical screening to determine their characteristics (absorption, excitation, and emission). The results confirmed the amorphous nature of the synthesized glass samples, while the FTIR revealed the existence of BO3, and BO4 vibrations in the samples. The series glass quality of LAGdxBSm1.0 doped in the host matrix was confirmed by the radioluminescence and photoluminescence results at the optimal doping concentration of 2.5 mol%. The decay of samples was investigated to determine the relationship between doping concentration and luminescence characteristics. Glasses have been created into an appropriate lighting glass using 25Li2 O-5Al2 O3 -2.5Gd2 O3 -(67.5-X)B2 O3 -XSm2 O3 host matrix glass doped with varying concentrations of Sm 3+ . Visible light and near-infrared absorption values in the glass samples demonstrate the existence of Sm 3+ ions. The photoluminescence and radioluminescence spectra have high concentration quenching (0.5 mol%) and produce four emission peak wavelengths, with the maximum emission wavelength at 600 nm (soft orange color). Based on these results, the studied glass series could be a good choice for X-ray scintillators in medical, industrial, and other settings in the future. Highlights: Gd 3+ /Sm 3+ co-doped in borate glasses were developed. The optimum concentration of Gd2 O3 was observed at 2.5 mol%. Sm2 O3 0.5 mol% is the quenching concentration confirmed by the luminescence. The XANES spectra confirmed the trivalent oxidation state of Sm.